Classification of pedogenic cementation in Podzols by pocket penetrometry. Issue 4 (27th June 2017) - Hirsch, Florian; Raab, Thomas; Heller, Sebastian; Bauriegel, Albrecht
Abstract: According to the German Soil Taxonomy, the formation of cemented horizons in Podzols is restricted to the precipitation of iron oxides. However, in iron‐poor sandy substrates, also illuviation of only organic compounds can form cemented horizons with penetration resistances of up to 14 kg cm −2 . We present a reproducible field test for classifying pedogenic cementation in Podzols and suggest considering cemented horizons (Bmh and Bhm) in the upcoming edition of the Guidelines for Soil Mapping.